1998
DOI: 10.1107/s0907444997019434
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Strong Patterson Function Signals in Many-Body Molecular Replacement

Abstract: The symmetry elements detected by the self-rotation and the Patterson functions, associated with strong correlations between the positions of the molecules in the asymmetric unit, are used to reduce the effective number of independent bodies to be located by the molecular replacement method. A distinction is made between 'frustrated' crystallographic symmetries, i.e.those that are almost crystallographic ones, and "standard' non-crystallographic symmetries, which are taken into account by specific techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Crystals belonged to space group C222 1 with one molecule per asymmetric unit. Molecular replacement (AMORE program [71] ) using data in the 40 to 3.0 resolution range and the HDM2 coordinates from the HDM2/p53(15-29) crystal structure (pdb-code: 1YCR) yielded significant solutions. The correctly positioned search model was refined to 1.9 resolution with the program REFMAC.…”
Section: Methodsmentioning
confidence: 99%
“…Crystals belonged to space group C222 1 with one molecule per asymmetric unit. Molecular replacement (AMORE program [71] ) using data in the 40 to 3.0 resolution range and the HDM2 coordinates from the HDM2/p53(15-29) crystal structure (pdb-code: 1YCR) yielded significant solutions. The correctly positioned search model was refined to 1.9 resolution with the program REFMAC.…”
Section: Methodsmentioning
confidence: 99%
“…Initial phases for the Lb pro (residues 29–201) crystal form were obtained by molecular replacement with the sLb pro coordinates as a model. Rotation/translation parameters were calculated with 95% of data between 15 and 3.5 Å using the AMoRe package (Navaza, 1994), and the information about the presence of a translational symmetry derived from the strong peak found in the native Patterson at position u = 0.5, v = 0.5, w = 0.225 (Navaza et al ., 1998). Four independent solutions were found that generate the second four by translation.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of A. fumigatus MnSOD was solved by molecular replacement using the program AMORE (22). The structure of the human MnSOD dimer (PDB ID 1ABM) (4), which shares 45% sequence identity with A.fumigatus MnSOD, was used as a search model.…”
Section: Molecular Replacementmentioning
confidence: 99%